Pengaruh Sukuk Korporasi dan Inflasi Terhadap Profitabilitas Bank Umum Syariah Selama Pandemi Covid-19 - Qulub, Ana Fidatul; Muhammad Alan Nur; Budi Sukardi (Jurnal Ekonomika dan Bisnis Islam, 2023)
The Covid-19 pandemic has had an impact on various sectors including the economy. In the Islamic capital market with corporate sukuk instruments, it shows an increase in the total outstanding value of 42%, while in Islamic Commercial Banks it shows an increase in ROA of 0.12%, both of which recorded growth. Supposedly, as an institution looking for investors the relationship they have is negative. On the other hand, the inflation rate in Indonesia during the pandemic has also increased quite high. So this study aims to examine the effect of corporate sukuk and inflation on the ROA of Islamic Commercial Banks during the Covid-19 pandemic. This research is a quantitative study using samples from January 2020-December 2022 with the help of e-views 12 software. Based on the results of the analysis, only corporate sukuk have a significant positive effect on Return on Assets of Islamic Commercial Banks, while inflation is not significant. Simultaneously, both have a significant positive effect on the Return on Assets (RO) of Islamic Commercial Banks. So for Islamic Commercial Banks it is necessary to pay attention to the existence of corporate sukuk and the inflation rate because it has an impact on ROA which will ultimately have an impact on the performance of the banking itself.